The Urgency of Enhancing Village Fund Governance in Serang Regency - Eko Prasetyo; Hunainah Hunainah; Rachmat Maulana (Kolaborasi : Jurnal Administrasi Publik, 2023)
The Law No. 6 of 2014 concerning Villages grants villages the authority to govern themselves, and the government allocates village funds for their implementation. In Serang Regency, there are issues regarding the ineffective governance of village funds, characterized by the low quality of human resources for public services, lack of transparency and accountability, and insufficient community empowerment programs. This study aims to emphasize the urgency of improving the governance of village funds towards better governance in Serang Regency. The research adopts a qualitative descriptive method. Key informants come from relevant agencies in Serang Regency, the Inspectorate, and civil society organizations, with information gathered through observations and focused group discussions. The research findings indicate that only the dimensions of resource management and governance process are categorized as sufficient, while decision-making, collaboration with the private sector, and other governance principles still need improvement. Based on the research findings, it can be concluded that the governance of village funds in Serang Regency requires urgent strengthening.